Eksplorasi Hasil Belajar Matematika melalui Penerapan Sistem Pembelajaran Daring (SIPEDAR) di Masa Pandemi Covid-19 - Trisniawati Trisniawati; Mahmudah Titi Muanifah; Nelly Rhosyida; Rosidah Aliim Hidayat (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2021)
This study aims to describe student learning outcomes through the application of the online learning system (SIPEDAR) during the COVID-19 pandemic and to find out what features are used in learning through SIPEDAR such as assignment (assignment), attendance (presence), bigbluebottonBN, choice, databases, external tools, feedback, forums, glossaries, quizzes, chats, quizzes, lessons, scrom packages, surveys, workshops, books, files, folders, IMS content packages, labels, pages, and URLs. This type of research is qualitative research. The subjects in this study were third semester students who took Mathematics at Elementary School Class High in the elementary school teacher education study program at Universitas Sarjanawiyata Tamansiswa. The instruments used were in the form of multiple choice questions, true false statements, and descriptions. The results of the study were the average quiz score and the average assignment score in class 3A, namely 83.27 and 72.90. The average quiz score and the average assignment score in the 3F class were 83.56 and 70.67. Student learning outcomes in both classes are included in the good category so that learning using SIPEDAR is carried out well and can be modified with other e-learning platforms.